Gestational diabetes induces autistic-like behaviors in offspring by disrupting the GABAergic system - Xuan-Qi Liu; Tian-li Huang; Shu-Yu Zhang; Yu-Tong Huang; Jia-Ying Mo; Yi-Shang Yan; Yi-Ning Cao; Yue-Ran Cai; Jian-Zhong Sheng; Hong Zhu; He Feng Huang (Frontiers in Neuroscience)
BackgroundIncreasing evidence have shown that gestational diabetes mellitus (GDM) is associated with the risk of autism in offspring. However, the underlying mechanisms have not yet been fully elucidated.MethodsA mouse model of gestational diabetes mellitus (GDM) was established to investigate its impact on offspring. Behavioral analyses were conducted to assess social novelty and stereotypic behaviors. Neuronal excitability in the prefrontal cortex (PFC) was evaluated using c-Fos staining after social behavior stimulation. Single-cell transcriptomics and metabolomics were employed to analyze changes in the GABAergic system.ResultsBehavioral analyses revealed that GDM led to impaired social novelty and increased stereotypic behaviors in male offspring. c-Fos staining showed hyperexcitability in the PFC of male offspring from the GDM group following social behavior stimulation. Single-cell transcriptomics and metabolomics identified alterations in the GABAergic system, including a decrease in GABAergic neurons and reduced GABA levels. This reduction in GABA was associated with decreased GAD2 expression due to DNA hypermethylation in the GAD2 promoter region.ConclusionThese data suggest that GDM induces autistic-like behaviors, including reduced social novelty and increased stereotypic behaviors, in offspring by affecting the GABAergic system. These findings provide new insights into how GDM may influence neurodevelopment in offspring.